Basal expression of insulin‐like growth factor 1 receptor determines intrinsic resistance of cancer cells to a phosphatidylinositol 3‐kinase inhibitor ZSTK474. Issue 2 (16th January 2015) - Isoyama, Sho; Kajiwara, Gensei; Tamaki, Naomi; Okamura, Mutsumi; Yoshimi, Hisashi; Nakamura, Naoki; Kawamura, Kento; Nishimura, Yumiko; Namatame, Nachi; Yamori, Takao; Dan, Shingo
<x xml:space="preserve">Abstract</x> Drug resistance often critically limits the efficacy of molecular targeted drugs. Although pharmacological inhibition of phosphatidylinositol 3‐kinase (PI3K) is an attractive therapeutic strategy for cancer therapy, molecular determinants for efficacy of PI3K inhibitors (PI3Kis) remain unclear. We previously identified that overexpression of insulin‐like growth factor 1 receptor (IGF1R) contributed to the development of drug resistance after long‐term exposure to PI3Kis. In this study, we examined the involvement of basal IGF1R expression in intrinsic resistance of drug‐naïve cancer cells to PI3Kis and whether inhibition of IGF1R overcomes the resistance. We found that cancer cells highly expressing IGF1R showed resistance to dephosphorylation of Akt and subsequent antitumor effect by ZSTK474 treatment. Knockdown of IGF1R by siRNAs facilitated the dephosphorylation and enhanced the drug efficacy. These cells expressed tyrosine‐phosphorylated insulin receptor substrate 1 at high levels, which was dependent on basal IGF1R expression. In these cells, the efficacy of ZSTK474 in vitro and in vivo was improved by its combination with the IGF1R inhibitor OSI‐906. Finally, we found a significant correlation between the basal expression level of IGF1R and the inefficacy of ZSTK474 in an in vivo human cancer panel, as well as in vitro. These results suggest that basal IGF1R expression affects intrinsic resistance of cancer cells to ZSTK474, and IGF1R is a promising target to improve the therapeutic efficacy. The current results provide evidence of combination therapy of PI3Kis with IGF1R inhibitors for treating IGF1R‐positive human cancers.